Salvage chemotherapy after progression on immunotherapy in recurrent/metastatic squamous cell head and neck carcinoma - Llop, Sandra; Plana, Maria; Tous, Sara; Ferrando-Díez, Angelica; Brenes, Jesús; Juarez, Marc; Vidales, Zara; Vilajosana, Esther; Linares, Isabel; Arribas, Lorena; Duch, Maria; Fulla, Marta; et al. (Frontiers in Oncology, 2024)
ObjectivesAnti-PD-(L)1 agents changed the landscape of recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC) treatment. Previous studies showed improved response rates to salvage chemotherapy (SCT) after progression to anti-PD-(L)1 agents. This study aims to evaluate the outcomes of SCT and to identify predictors of response and survival in patients with R/M HNSCC.Materials and methodsRetrospective cohort analysis of 63 R/M patients treated with SCT after antiPD-(L1)-based therapy between January 2015 and August 2022. The overall response rate (ORR) was evaluated. Progression-free survival (PFS) and overall survival (OS) were estimated with Kaplan–Meier method. Progression-free survival 2 was calculated from anti-PD-(L)1-therapy start until progression to SCT (PFS2-I). Logistic regression and Cox regression analyses were performed to identify predictors of outcome.ResultsA total of 63 patients were included: 76% were men, and median age was 60 years. PD-L1 status was available in 68% (61% positive). Up to 71% received SCT as third line or beyond. ORR to SCT was 49% with higher rates in PD-L1 positive tumors, 71% vs. 18% (p=0.001), and cetuximab-containing regimens, 68% vs. 39% (p=0.026). PD-L1 status was the only predictor of ORR in the adjusted model (OR=8.6, 95% CI 1.7–43.0). OS and PFS were 9.3 months (95% CI, 6.5–12.3) and 4.1 months (95% CI, 3.0–5.8) respectively. PFS2-I was 8.6 months (95% CI, 6.6–10.5). In the multivariate analysis, PD-L1 was the only independent factor for OS (HR=0.3; 95% CI, 0.1–0.7), PFS (HR=0.2; 95% CI, 0.1–0.5; p<0.001), and PFS2-I (HR=0.2; 95% CI 0.1–0.5; p<0.001).ConclusionPDL1 status appeared as a strong predictor of response of efficacy for SCT after anti-PD-(L)1 agents. Patients receiving cetuximab-containing regimens trended towards greater benefit. This highlights the importance of treatment sequencing and personalized treatment strategies.